Genetic variabilities and relationships among some egyptian Aspergillus spp. based on microscopic characters, isozyme profiles and random amplification of polymorphic DNA - Gaber, Elham; Hosseiny, Manal M; Abo-Elmagd, Heba I (Bangladesh Journal of Botany, 2018)
Twelve Aspergillus spp. were isolated from the Egyptian soils and were studied morphologically and microscopically. Isozyme profiles and random amplified polymorphic DNA (RAPD) were also employed for determination of the genetic relationship among the tested Aspergillus spp. Results of RAPD revealed genetic similarity level above 80% between A. terreus and A. aculeatus. The species A. niger, A. candidus, A. terreus and A. aculeatus were joined with a similarity level of 65%. Unique bands were displayed by certain fungi and can be taken as a positive marker for isolate identification. Five isozyme systems; peroxidase, alcohol dehydrogenase, α esterase, β esterase and superoxide dismutase were studied to detect the genetic variabilities among the tested isolates. Subsequently, comparing the three dendrograms which belong to morphological characters, isoymes and RAPD revealed a great relationship between A. terreus and A. niveus from one side and A. candidus and A. terreus from the other side.